Urine excretion strategy for stem cell-generated embryonic kidneys - Yokote, Shinya (Proc Natl Acad Sci U S A, 2015)
There have been several recent attempts to generate, de novo, a functional whole kidney from stem cells using the organogenic niche or blastocyst complementation methods. However, none of these attempts succeeded in constructing a urinary excretion pathway for the stem cell-generated embryonic kidney. First, we transplanted metanephroi from cloned pig fetuses into gilts; the metanephroi grew to about 3 cm and produced urine, although hydronephrosis eventually was observed because of the lack of an excretion pathway. Second, we demonstrated the construction of urine excretion pathways in rats. Rat metanephroi or metanephroi with bladders (developed from cloacas) were transplanted into host rats. Histopathologic analysis showed that tubular lumina dilation and interstitial fibrosis were reduced in kidneys developed from cloacal transplants compared with metanephroi transplantation. Then we connected the host animal’s ureter to the cloacal-developed bladder, a technique we called the “stepwise peristaltic ureter” (SWPU) system. The application of the SWPU system avoided hydronephrosis and permitted the cloacas to differentiate well, with cloacal urine being excreted persistently through the recipient ureter. Finally, we demonstrated a viable preclinical application of the SWPU system in cloned pigs. The SWPU system also inhibited hydronephrosis in the pig study. To our knowledge, this is the first report showing that the SWPU system may resolve two important problems in the generation of kidneys from stem cells: construction of a urine excretion pathway and continued growth of the newly generated kidney.